Content validity evidences in the motor coordination test with ball - Schelyne Ribas; Layla Maria Campos Aburachid; Juan Carlos Pérez Morales; Gabriella Nelli Monteiro; Gibson Moreira Praça; Henrique Oliveira Castro; Pablo Juan Greco (Universidade Federal de Santa Catarina, 2020)
The main objective of this study was to establish content validity evidences in the Motor Coordination Test with Ball (MCTB). Four Ph.D. professors and former sports coaches with academic experience in the motor coordination area took part of the validation process as experts. The experts assessed four motor tasks and graded using the Likert scale from one to five for criteria of clarity of language, practice relevance, and theoretical relevance. The content validity coefficient (CVC) has been used to determine the CVCc of each task and the CVCt for the instrument as a whole, adopting as a cutoff CVCc .70 and CVCt .80. The results showed good agreement among experts concerning "clarity of language" (CVC= .89), "practice relevance" (CVC= .81), and theoretical relevance (CVC= .86). For "practice relevance" of images and videos of task execution, there has been observed CVCt of .86 and CVCt of .95, respectively. When requested the order of relevance of coordination pressures, the agreement among experts presented the existence of at least four coordination pressures in each one of the tasks and, out of these, at least two had a higher relevance. After the calculation of the CVC, ecological validity was determined for the MCTB, accrediting it as an instrument for the assessment of motor coordination with ball in the context of sports games.